The role of Kefalovruso and Amourio springs in the hydrodynamic conditions of Potamia Elassona Basin - Vasileiou, E.; Koumantakis, I. (Bulletin of the Geological Society of Greece, 2013)
Elassona area in central Greece. The water resources of the region affect critically the exploitation of the mineral deposits. The detailed hydrogeological research of the area is imperative before starting the mining activities. Two groups of springs discharge near the study area. The karstic springs of Kefalovruso are in the northwest boundaries of the Neogene basin and the springs of Amourio are located in the Quaternary alluvial deposits, in the central part of the area. This paper includes the analysis of the hydrogeological conditions of the springs, the processing of the water- measurements (water supply, water level) and their correlation with the area’s meteorological data. The time series of hydrological data, from 1972 to 2008, were evaluated for both springs and several parameters were estimated in order to investigate the function and the capacity of the springs. The relation between the recharge system of the springs and the area’s groundwater dynamics is also analysed.